Pemanfaatan Limbah Sampah Sebagai Energi Alternatif Pembangkit Tenaga Listrik di Semarang - Sukarno Budi Utomo; Rita Hariningrum (Universitas Ivet, 2020)
The need for electrical energy in Indonesia is increasing every year so other alternative energy sources need to be found. Waste is a major problem for residents of many cities, along with the rate of population growth which has an impact on the increasing amount of waste generated. To explore the potential of new renewable energy, namely the construction of a Waste Power Plant (PLTSa). Potential of waste energy in Jatibarang Landfill sourced from 16 sub-districts of Semarang City Region has a large amount of waste production, so that in this study research needs to be done on the use of waste as an alternative energy source to be utilized as Renewable Energy (EBT) to be managed into electrical energy that is useful for the community. From this study the electrical energy that can be utilized for PLTSa in 1 year for the next 5 years (2017 - 2021) is 84,627.02 Mwh / year in 2017, then 82,308.43 Mwh / year in 2018, after that 83,627.97 Mwh / year in 2019, then 83,179.35 Mwh / year in 2020, and finally 83,434.88 in 2021. The average output power of generators is 9,525.63 kW as potential electrical energy from waste waste.